2009
DOI: 10.1186/1475-2891-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition prevalence and precision in nutritional care differed in relation to hospital volume – a cross-sectional survey

Abstract: Background: To explore the point prevalence of the risk of malnutrition and the targeting of nutritional interventions in relation to undernutrition risk and hospital volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 18 publications
2
29
1
Order By: Relevance
“…Assessment of nutritional status based on BMI, recent weight loss, and low energy intake has already been made by other studies with hospitalized (9,12), pre-operative and post-operative patients (32). A multicentric study that assessed nutritional status and clinical outcomes found an HEI/ER <75% rate of 32.4% (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of nutritional status based on BMI, recent weight loss, and low energy intake has already been made by other studies with hospitalized (9,12), pre-operative and post-operative patients (32). A multicentric study that assessed nutritional status and clinical outcomes found an HEI/ER <75% rate of 32.4% (24).…”
Section: Discussionmentioning
confidence: 99%
“…Different parameters are being developed to assess the nutritional status of hospitalized patients and better map this reality (5-9). Nevertheless, malnutrition is still underreported (10), despite its association with increased morbidity, mortality, and hospital costs (10).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in Sweden, 12 the prevalence of moderate and severe malnutrition varied from 22% to 34% in small, medium, and large hospitals.…”
mentioning
confidence: 95%
“…It has been shown that by having students to participate in the research process their attitudes towards research gets more positive [6] and that their research skills improve [6,7] . We have involved undergraduate nursing students in actual research projects since 2005 [2,[8][9][10] . For example, in a small study were the students (n=42) were research collaborators in a nutrition study, 86% stated that they got improved understanding of research and 38% got increased knowledge about nutrition [11] .…”
Section: Introductionmentioning
confidence: 99%